Where’s the Archivist in Digital Curation? Exploring the Possibilities through a Matrix of Knowledge and Skills - Lee, Christopher A.; Tibbo, Helen (Archivaria, 2011)
In recent years, the concept of digital curation has served as an umbrella spanning activities across a diversity of professions, institutions, actors, and sectors. We summarize the motivation, principles, methodology, and data that have served as the basis for the DigCCurr Matrix of Digital Curation Knowledge and Skills, and elaborate its six dimensions: 1) mandates, values, and principles; 2) functions and skills; 3) professional, disciplinary, or institutional/organizational context; 4) type of resource; 5) prerequisite knowledge; and 6) transition point in the information continuum. We explain how the Matrix can support the identification and organization of material to be addressed in professional education programs. This detailed articulation of digital curation activities reveals numerous opportunities to promote, advance, and further enhance the skills and capabilities of archivists. We present aspects of the DigCCurr Matrix that intersect with long-standing, archival competencies as well as discussing areas of potential growth and collaboration. Finally, we explain how expanding one’s professional focus from digital preservation to the wider universe of digital curation is similar and complementary to the move toward postcustodial and continuum approaches within the archival profession. We elaborate areas in which archivists can take advantage of these connections to advance the archival enterprise. RÉSUMÉ Depuis quelques années, le concept de la conservation numérique (« digital curation ») recouvre des activités englobant une vaste étendue de professions, d’institutions, de joueurs et de secteurs. Dans cet article, les auteurs font le résumé des intentions, des principes, des méthodologies et des données qui ont servi de base à la DigCCurr Matrix of Digital Curation Knowledge and Skills et élaborent ses six dimensions : 1) les mandats, valeurs et principes; 2) les fonctions et compétences; 3) le contexte professionnel, disciplinaire ou institutionnel/organisationnel; 4) le type de ressource; 5) les connaissances prérequises; 6) le point de transition dans le continuum de l’information. Ils expliquent comment la matrice peut appuyer l’identification et l’organisation du matériel dont il sera question dans les programmes d’éducation professionnelle. Cette énonciation détaillée des activités de la conservation numérique révèle de nombreuses occasions pour promouvoir, développer et parfaire davantage les compétences et habiletés des archivistes. Les auteurs présentent des aspects de la DigCCurr Matrix qui croisent les compétences archivistiques bien établies, tout en présentant des domaines de croissance et de collaboration potentielles. Enfin, ils expliquent comment l’élargissement du champ professionnel à partir de la préservation numérique (« digital preservation ») vers l’univers plus vaste de la conservation numérique ressemble et complète le mouvement vers des approches fondées sur le continuum des documents et le dépassement de la conservation (« postcustodialism »). Les auteurs élaborent enfin sur les domaines dans lesquels les archivistes pourraient prendre avantage de ce changement.